Saccular aneurysm formation of the descending aorta associated with aortic coarctation in an infant - Özyüksel, Arda; Cantürk, Emir; Dindar, Aygün; Akçevin, Atıf (Sociedade Brasileira de Cirurgia Cardiovascular, 2014)
Aneurysm of the descending aorta associated with CoA is an extremely rare congenital abnormality. In this report, we present a 16 months old female patient in whom cardiac catheterization had been performed which had revealed a segment of coarctation and saccular aneurysm in the descending aorta. The patient was operated and a 3x2 centimeters aneurysm which embraces the coarcted segment in descending aorta was resected. In summary, we present a case of saccular aortic aneurysm distal to aortic coarctation in an infant without any history of intervention or vascular inflammatory disease. Our case report seems to be the youngest patient in literature with this pathology.

Aneurisma da aorta descendente associada à coarctação aórtica é uma anomalia congênita extremamente rara. Neste relato, apresentamos uma paciente de 16 meses de idade, nos quais o cateterismo cardíaco foi realizado, que havia revelado um segmento de coarctação e aneurisma sacular na aorta descendente. A paciente foi operada e um aneurisma de 3x2 centímetros, englobando o segmento coarctada na aorta descendente foi ressecado. Em resumo, apresentamos um caso de aneurisma sacular distal à coarctação da aorta em uma criança sem histórico de intervenção ou doença inflamatória vascular. Nosso caso parece ser o do paciente mais jovem na literatura com esta afecção.
Formação de aneurismas saculares da aorta descendente associados com coarctação aórtica em criança
WOS: 000350904300023
PubMed ID: 25714219
Keywords: Aortic Aneurysm, Thoracic; Aortic Coarctation; Infant; Aneurisma da Aorta Torácica; Coarctação Aórtica; Lactente